Answer:
StartFraction StartRoot 3 EndRoot Over 3 EndFraction
Step-by-step explanation:
see the attached figure to better understand the problem
step 1
we know that
In the right triangle XYZ
---> adjacent side divided by the hypotenuse
substitute the values
Remember that
so
substitute
step 2
--> opposite side divided by the hypotenuse
substitute the values
Remember that
so
step 3
--> opposite side divided by adjacent side
substitute the values
Simplify
so
StartFraction StartRoot 3 EndRoot Over 3 EndFraction